Effectiveness of Communication and Results of Learning IV Class School Students on IPA Learning Through the Open Ended Model - Rifa Amri Zona; Hendra Syarifuddin (International Journal of Educational Dynamics, 2019)
This type of research is class action, with the subject of fourth grade elementary school students. The study was conducted in the even semester of the 2015/2016 academic year, the research instrument used was the effectiveness of communicating student sheets, learning outcome assessment sheets on the cognitive aspects of students at the level of knowledge and understanding. Based on the results of the study, the communication effectiveness of students in the first cycle obtained an average value of 49.99% increase in the second cycle to 67.45%, the communication effectiveness of students in the first cycle obtained an average value of 53.96% increasing in the second cycle to 71 , 42%. While student learning outcomes at the cognitive level of knowledge in the first cycle increased in the second cycle 68.33 to 80.47, cognitive learning outcomes at the level of understanding in the first cycle increased in the second cycle 58.09 to 71.42. It can be concluded that the Open Ended model can increase the effectiveness of communication and student learning outcomes in fourth grade science learning in elementary school.